Broadband manipulation of flexural waves based on phase-modulated elastic metasurfaces. (15th January 2023) - Hu, Yabin; Li, Meizhen; Liu, Hongbo; Li, Bing
Highlights: A furry of metasurface strategies are developed to realize extraordinary flexural wave manipulations. A theoretical model of effective phase velocity is proposed for explaining the broadband feature of metasurfaces. The proposed metasurfaces possess great superiorities in broad bandwidth, ultrathin footprint and powerful ability. The anomalous wave manipulation capabilities are systematically verified by theoretical prediction, numerical simulation and experimental testing. Abstract: As an innovative planar artificial structure, elastic metasurface exhibits great potential in the application fields of vibration and noise control. By virtue of the superior performance of compact/ultra-thin configuration, easy-fabrication and richer physics, metasurfaces are expected to make up for the deficiency of traditional metamaterials. However, achieving broadband exotic elastic-wave manipulations by using metasurfaces remains a highly desired feature. Here, on basis of a classical zigzag topology, we developed various elastic metasurface designs for broadband flexural wave tailoring at a sub-wavelength scale. By tuning the gradient phase shift, a series of extraordinary wavefront manipulation phenomena have been realized, including anomalous refraction, energy focusing, source transformation and self-accelerating beam. Remarkably, numerical and experimental results show that this design possesses absolute advantages of broadband, compact and high efficiency compared with the locally resonant strategy. This work may offer more thriving avenues for vibration and noise control in advanced structures.